The Semantic Web 20th International Conference, ESWC 2023, Hersonissos, Crete, Greece, May 28-June 1, 2023, Proceedings - Pesquita, Catia; Jimenez-Ruiz, Ernesto; McCusker, Jamie; Faria, Daniel; Dragoni, Mauro; Dimou, Anastasia; Troncy, Raphael; Hertling, Sven. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 20th International Conference on The Semantic Web, ESWC 2023, held in Hersonissos, Crete, Greece, during May 28-June 1, 2023. The 41 full papers included in this book were carefully reviewed and selected from 167 submissions. They are organized in topical sections as follows: research, resource and in-use.
Research -- Explainable Phenotype-Centric Drug Repurposing via Deep Reinforcement Learning -- A Comparative Study of Stream Reasoning Engines -- Join Ordering of SPARQL Property Path Queries -- Rening Large Integrated Identity Graphs using the Unique Name Assumption -- Structural Bias in Knowledge Graphs for the Entity Alignment Task -- A Framework to Include and Exploit Probabilistic Information in SHACL Validation Reports -- Transformer based Semantic Relation Typing for Knowledge Graph Integration -- Entity Linking for KGQA Using AMR Graphs -- REGNUM: Generating Logical Rules with Numerical Predicates in Knowledge Graphs -- Classifying sequences by combining context-free grammars and OWL ontologies -- NASTyLinker: NIL-Aware Scalable Transformer-based Entity Linker -- iSummary: Workload-based, Personalized summaries for Knowledge Graphs -- Neural Class Expression Synthesis -- Evaluating Language Models for Knowledge Base Completion -- Subsumption Prediction on E-Commerce Taxonomies -- Two-view Graph Neural Networks for Knowledge Graph Completion -- GETT-QA: Graph Embedding based T2T Transformer for Knowledge Graph Question Answering -- Repairing EL ontologies using weakening and completing -- Activity Recommendation for Business Process Modeling with Sequence-to-Sequence Models -- Resource -- RELD: A Knowledge Graph of Relation Extraction Datasets -- The Internet Meme Knowledge Graph -- Describing and Organizing Semantic Web and Machine Learning Systems in the SWeMLS-KG -- A Concise Ontology to Support Research on Complex, Multimodal Clinical Reasoning -- LauNuts: A Knowledge Graph to identify and compare geographic regions in the European Union -- HHT : an approach for representing temporally-evolving historical territories -- An Upper Ontology for Modern Science Branches and Related Entities -- K-Hub: a modular ontology to support document retrieval and knowledge extraction in Industry 5.0 -- pyRDF2Vec: A Python Implementation and Extension of RDF2Vec -- Boosting Knowledge Graph Generation from Tabular Data with RML Views -- A knowledge graph of contentious terminology for inclusive representation of cultural heritage -- LegalHTML: a Representation Language for Legal Acts -- Whyis 2: An Open Source Framework for Knowledge Graph Development and Research -- In-Use -- Prototyping an End-User User Interface for the Solid Application Interoperability Specication under GDPR -- SemReasoner - A high-performance Knowledge Graph Store and rule-based Reasoner -- LIS: A Knowledge Graph-based Line Information System -- Combining Semantic Web and Machine Learning for Auditable Legal Key Element Extraction -- Understanding Customer Requirements - an Enterprise Knowledge Graph Approach -- Investigating Ontology-based data access with GitHub -- Enabling Live SPARQL Queries Over ConceptNet Using Triple Pattern Fragments -- Evaluation of a Representative Selection of SPARQL Query Engines using Wikidata -- MOSAIK: An Agent-Based Decentralized Control System with Stigmergy For A Transportation Scenario.
Keywords: Information storage and retrieval systems; Information Storage and Retrieval